2021
DOI: 10.1155/2021/5544599
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Fetal Abdominal Wall Thickness and Intrapartum Complications amongst Mothers with Pregestational Type 2 Diabetes

Abstract: Objectives. To evaluate the utility of fetal abdominal wall thickness (AWT) for predicting intrapartum complications amongst mothers with pregestational type 2 diabetes. Methods. This was a historical cohort study of pregnant mothers with pregestational type 2 diabetes delivering at a Canadian tertiary-care center between January 1, 2014, and December 31, 2018. Delivery records were reviewed to collect information about demographics and peripartum complications. Stored fetal ultrasound images from 36 weeks’ ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Increase in the prevalence of pre-gestational diabetes is expected to lead to the increase in the prevalence of all associated pregnancy complications affecting the mothers and the newborns, such as miscarriages, Caesarean deliveries, lacerations during vaginal deliveries, venous thromboembolism, congenital malformations, perinatal asphyxia and an overall higher perinatal mortality [ 15 , 16 , 17 ]. All of these complications are associated with the higher likelihood for increase in the length of hospital stay and the increase in the health care required for each women and the newborn [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increase in the prevalence of pre-gestational diabetes is expected to lead to the increase in the prevalence of all associated pregnancy complications affecting the mothers and the newborns, such as miscarriages, Caesarean deliveries, lacerations during vaginal deliveries, venous thromboembolism, congenital malformations, perinatal asphyxia and an overall higher perinatal mortality [ 15 , 16 , 17 ]. All of these complications are associated with the higher likelihood for increase in the length of hospital stay and the increase in the health care required for each women and the newborn [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…We were limited to data available up to the time of the midpregnancy ultrasound and recorded in our ultrasound charts, and did not have information about late pregnancy complications. However, another study from our group showed no relationship between fetal abdominal wall thickness and the risk of cesarean section or shoulder dystocia [ 26 ]. Further research is needed to evaluate the influence of glycemic control, other maternal exposures (including gestational versus type 1 diabetes), ethnicity/HNF1 α genotype, and preeclampsia on fetal renal development and fat metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the known association between childhood obesity and youthonset T2D, little attention has been paid to fetal fat distribution beyond overall fetal growth or macrosomia. With increasing awareness of the developmental origins of health and disease (DOHaD), there is speculation as to whether fetal renal injury and/or metabolic changes may already begin in utero for offspring of mothers with diabetes [22,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, definitions of macrosomia using an absolute birth weight instead of a percentile corrected for gestational age underestimate the identification of largeforgestational age infants. 11,33,34 Largeforgestationalage size is associated with an increased risk of other adverse pregnancy outcomes such as neonatal hypoglycemia and stillbirth. 3,31,35 Both dia betes in pregnancy and fetal macrosomia are also independent predictors of cesarean delivery, which is consistent with our study finding that type 2 diabetes increased risk of cesarean delivery.…”
Section: Discussionmentioning
confidence: 99%